2009
DOI: 10.1002/bmc.1347
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of acetylcholine, an essential neurotransmitter, in brain microdialysis samples by liquid chromatography mass spectrometry

Abstract: Chemical neurotransmission has been the subject of intensive investigations in recent years. Acetylcholine is an essential neurotransmitter in the central nervous system as it has an effect on alertness, memory and learning. Enzymatic hydrolysis of acetylcholine in the synaptic cleft is fast and quickly metabolizes to choline and acetate by acetylcholinesterase. Hence the concentration in the extracellular fluid of the brain is low (0.1-6 nm). Techniques such as microdialysis are routinely employed to measure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 72 publications
2
38
0
Order By: Relevance
“…Microdialysis, with its collection times on the scale of several seconds to minutes, may allow for more ACh hydrolysis by acetylcholinesterase, resulting in lower reported concentrations. Thus, many scientists who use microdialysis for measuring ACh levels also perfuse an acetylcholinesterase inhibitor, such as neostigmine, to prevent ACh breakdown (Nirogi et al, 2010; Ragozzino et al, 1996). However, this technique may artificially affect the measured ACh levels in the extracellular space.…”
Section: Discussionmentioning
confidence: 99%
“…Microdialysis, with its collection times on the scale of several seconds to minutes, may allow for more ACh hydrolysis by acetylcholinesterase, resulting in lower reported concentrations. Thus, many scientists who use microdialysis for measuring ACh levels also perfuse an acetylcholinesterase inhibitor, such as neostigmine, to prevent ACh breakdown (Nirogi et al, 2010; Ragozzino et al, 1996). However, this technique may artificially affect the measured ACh levels in the extracellular space.…”
Section: Discussionmentioning
confidence: 99%
“…The ACh peak had a bad shape and width in a simultaneous determination of multiple neurotransmitters [23]. Furthermore, the researchers analyzing ACh with MS detector have been listed in a review [24]. There were various columns and mobile phases for detection of ACh and the best LLOQ was 1 fmol on column.…”
Section: Introductionmentioning
confidence: 99%
“…ESI-MS/MS has been extensively used for the determination of endogenous biomarkers due to its high sensitivity and selectivity [16,27,28]. The ACh, HA, t-mHA, and t-MIAA molecules studies here all contain basic amine functionalities that allows for positive charging under acidic conditions and results in sufficient sensitivity using the ESI positive ionization mode without derivatization.…”
Section: Uplc-ms/ms Assay Developmentmentioning
confidence: 99%
“…While analytical methodologies on the quantitative analysis of neurotransmitters in rat brain microdialysates have been extensively reported [16,18,27,37], only a few studies have analyzed their concentrations in the CSF [8]. Although in vivo microdialysis is used in preclinical studies to assess the release of neurotransmitters, the translation of these findings from preclinical to clinical studies has yet to be demonstrated.…”
Section: Stability Assessmentmentioning
confidence: 99%